2007
DOI: 10.1111/j.1365-246x.2007.03382.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of thermal conductivity, thermal diffusivity and specific heat in sI methane hydrate

Abstract: S U M M A R YThermal conductivity, thermal diffusivity and specific heat of sI methane hydrate were measured as functions of temperature and pressure using a needle probe technique. The temperature dependence was measured between −20 • C and 17 • C at 31.5 MPa. The pressure dependence was measured between 31.5 and 102 MPa at 14.4 • C. Only weak temperature and pressure dependencies were observed. Methane hydrate thermal conductivity differs from that of water by less than 10 per cent, too little to provide a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
178
5
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(195 citation statements)
references
References 43 publications
6
178
5
2
Order By: Relevance
“…With respect to temperature effect, many studies found that hydrates exhibit a glass-like temperature dependence of thermal conductivity (Andersson and Ross, 1983;Handa and Cook, 1987;Krivchikov et al, 2005Krivchikov et al, , 2006Ross et al, 1981;Ross and Andersson, 1982;Tse and White, 1988). Among these studies, the works of Krivchikov et al (2005Krivchikov et al ( , 2006 are interesting as they found that both methane and xenon hydrates show crystal-like temperature dependence below 90 K, while exhibiting glass-like behavior above 90 K. The effect of pressure has also been investigated by many groups (Andersson and Ross, 1983;Rosenbaum et al, 2007;Waite et al, 2007). Only weak pressure dependency was observed by them.…”
Section: Thermal Conductivity Of Gas Hydratementioning
confidence: 96%
See 1 more Smart Citation
“…With respect to temperature effect, many studies found that hydrates exhibit a glass-like temperature dependence of thermal conductivity (Andersson and Ross, 1983;Handa and Cook, 1987;Krivchikov et al, 2005Krivchikov et al, , 2006Ross et al, 1981;Ross and Andersson, 1982;Tse and White, 1988). Among these studies, the works of Krivchikov et al (2005Krivchikov et al ( , 2006 are interesting as they found that both methane and xenon hydrates show crystal-like temperature dependence below 90 K, while exhibiting glass-like behavior above 90 K. The effect of pressure has also been investigated by many groups (Andersson and Ross, 1983;Rosenbaum et al, 2007;Waite et al, 2007). Only weak pressure dependency was observed by them.…”
Section: Thermal Conductivity Of Gas Hydratementioning
confidence: 96%
“…Regarding to measurement technique, the most widely adopted ones are standard needle probe technique and transient plane source (TPS) technique (Gustafsson et al, 1979(Gustafsson et al, , 1986. For example, thermal conductivity of methane hydrate has been determined by deMartin (2001), Krivchikov et al (2005), and Waite et al (2007) using the needle probe technique. With same technique, thermal conductivities of several other gas hydrates, such as tetrohydrofuran (THF) hydrate (Cortes et al, 2009), xenon hydrate (Krivchikov et al, 2006), HCFC-141b hydrate , and CFC-11 hydrate ) have been measured.…”
Section: Thermal Conductivity Of Gas Hydratementioning
confidence: 99%
“…As shown in Table, the thermal conductivities of methane hydrate and water differ by <10% at the temperatures found in hydrate-bearing sediments [48,49]. For this reason, firstorder thermal conductivity estimates can neglect the presence of methane hydrate and assume the sediment pore space contains only water [50].…”
Section: Thermal Propertiesmentioning
confidence: 99%
“… When we discretize in space and in time eqn (9) becomes: (10) 4) The new temperature at each point is determined in accordance with the enthalpy diagram of Figure 4 The values used for the different material properties taken from Gupta et al [10] and Waite et al [11] are: for methane hydrates: latent heat=438540 (joules/kg), specific heat=2108 joules/(kg K), density=913 kg/(m 3 ), and thermal conductivity=0.5 watts/(m.K) for water: specific heat=4187 joules/(kg.K), density=1000 kg/(m 3 ), and thermal conductivity=0.58 watts/(m.K)…”
Section: Solutions Inside the Reservoirmentioning
confidence: 99%